SARS-CoV-2 Infections in Italian Schools: Preliminary Findings After 1 Month of School Opening During the Second Wave of the Pandemic - Buonsenso, Danilo; De Rose, Cristina; Moroni, Rossana; Valentini, Piero (Frontiers in pediatrics, 2021)
Introduction: The impact of school opening on the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is still unknown. This study aims to provide preliminary information about the number of SARS-CoV-2 cases among students attending Italian schools. Methods: Data are extracted and analyzed from an open-access, online dataset that monitor, on a daily basis, media news about SARS-CoV-2 infections of students attending Italian schools. Results: As of October 5, 2020, a total of 1,350 cases of SARS-CoV-2 infections have been registered in the Italian territory schools (involving 1,059 students, 145 teachers, and 146 other school members), for a total of 1,212 out of 65,104 (1.8%) Italian schools involved. National schools reported only one case of SARS-CoV-2 infection in more than 90% of cases, and only in one high school a cluster of more than 10 cases has been described ( P = 0.015). The detection of one or more SARS-CoV-2 infections led to the closure of 192 (15.8%) entire schools, more frequently nursery/kindergartens ( P < 0.0005). Discussion: Our preliminary data support low transmission of SARS-CoV-2 within schools, at least among younger students. However, entire schools are frequently closed in the fear of larger outbreaks. Continuous monitoring of school settings, hopefully through daily updated open-access datasets, is needed to better understand the impact of schools on the pandemic and provide guidelines that better consider different risks within different age groups.